Cryptocurrency portfolio optimization - Baigaliyeva, Madina; Borovička, Adam; Pelikán, Jan, 1943-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
Nowadays, investments are solid opportunities to keep or even multiply savings. More and more people are thinking about investing in cryptocurrency, because they want to earn or because they believe that someday cryptocurrency can completely substitute traditional currency. Many researchers devoted their work to portfolio selection theory. Mathematical modeling allows to apply these theories on actual dataset. The aim of this thesis is to construct cryptocurrency portfolio using mathematical models. To achieve the aim the objectives were set; firstly, to analyze cryptocurrency market, then to examine Mean-Variance and Mean-Semivariance models, finally, to apply models on dataset. This thesis, firstly, discloses short description of dataset, Bitcoin history, blockchain and mining and wallets and exchanges. Then it describes some statistical definitions and notions, afterwards Mean-Variance and Mean-Semivariance models are mathematically depicted and examined. Finally, mathematical models are applied on actual dataset. Two approaches to the models were examined: risk minimization and return maximization. We considered three terms: daily investments, monthly investments and annual investments. To sum up, portfolio constructed for investments on daily basis barely achieves 0% return at the high level of risk, according to Mean-Variance and Mean-Semivariance models. Monthly investments portfolios are loss-making, however investing in cryptocurrency for long-term can be beneficial. Risk-free portfolio has positive return, high risk portfolio has high return respectively. In result, we depicted Efficient Frontier and tables with weights of single asset for each model, so that investor can chose according to preferences.
Vedoucí práce: Adam Borovička
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses